miRNA and mRNA Profiling Links Connexin Deficiency to Deafness via Early Oxidative Damage in the Mouse Stria Vascularis - Gentile, Giulia; Paciello, Fabiola; Zorzi, Veronica; Spampinato, Antonio Gianmaria; Guarnaccia, Maria; Crispino, Giulia; Tettey-Matey, Abraham; Scavizzi, Ferdinando; Raspa, Marcello; Fetoni, Anna Rita; Cavallaro, Sebastiano; Mammano, Fabio (Frontiers in Cell and Developmental Biology, 2021)
Pathogenic mutations in the nonsyndromic hearing loss and deafness 1 (DFNB1) locus are the primary cause of monogenic inheritance for prelingual hearing loss. To unravel molecular pathways involved in etiopathology and look for early degeneration biomarkers, we used a System Biology approach to analyze Cx30-/- mice at an early cochlear post-natal developmental stage and. These mice are a DFNB1 mouse model with severely reduced expression levels of two connexins in the inner ear, Cx30 and Cx26. Integrated analysis of miRNA and mRNA expression profiles in the cochlea of Cx30-/- mice at postnatal day 5 revealed the overexpression of five miRNAs (miR-34c, miR-29b, miR-29c, miR-141, and miR-181a) linked to apoptosis, oxidative stress and cochlear degeneration, which have Sirt1 as a common target of transcriptional and/or post-transcriptional regulation. In young adult Cx30-/- mice (3 months of age) these alterations culminated with blood barrier disruption in the stria vascularis (SV), which is known to have the highest aerobic metabolic rate of all cochlear structures, and whose microvascular alterations contribute to age-related degeneration and progressive decline of auditory function. Our experimental validation of selected targets links hearing acquisition failure in Cx30-/- mice, early oxidative stress and metabolic dysregulation to the activation of the Sirt1-p53 axis. This is the first integrated analysis of miRNA and mRNA in the cochlea of the Cx30-/- mouse model, providing evidence that connexins downregulation determines a miRNA-mediated response which leads to chronic exhaustion of cochlear antioxidant defense mechanisms and consequent SV dysfunction. Our analyses support the notion that connexins dysfunction intervenes early on during development, causing vascular damage later on in life. This study identifies also early miRNA-mediated biomarkers of hearing impairment, either inherited or age-related.